2017
DOI: 10.1177/2151458517720991
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Total Hip Arthroplasty Versus Hemiarthroplasty in the Management of Geriatric Femoral Neck Fractures

Abstract: Introduction:Recent clinical evidence suggests that total hip arthroplasty (THA) provides improved clinical outcomes as compared to hemiarthroplasty (HA) for displaced femoral neck fractures in elderly individuals. However, THA is still utilized relatively infrequently. Few studies have evaluated the factors affecting utilization and the role socioeconomics plays in THA versus HA.Methods:In the United States, the National Inpatient Sample (NIS) database was used to identify patients treated surgically for femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…There is still an ongoing debate whether DM or HA has better advantages for displaced femoral neck fractures in older population. 7,9 To our knowledge, this is the first study to evaluate the HHS for a period of 3 years tending to prove this parameter in long-term approach compared to other studies. The results of this study show that DM has better primary outcome compared to HA.…”
Section: Discussionmentioning
confidence: 64%
“…There is still an ongoing debate whether DM or HA has better advantages for displaced femoral neck fractures in older population. 7,9 To our knowledge, this is the first study to evaluate the HHS for a period of 3 years tending to prove this parameter in long-term approach compared to other studies. The results of this study show that DM has better primary outcome compared to HA.…”
Section: Discussionmentioning
confidence: 64%
“…Dangelmajer et al reported that Asian or Pacific Islander patients had significantly lower rates of THA for femoral neck fractures compared with White patients (OR = 0.507; 95% CI, 0.330 to 0.778; p = 0.0019), but other races/ethnicities did not differ 18 . Gwam et al analyzed the National Inpatient Sample database for patients who underwent TKA between 2009 and 2015 and reported that, in addition to an overall increase in the TKA utilization rate, there was an increase in minority representation among recipients, the highest being in Black patients (+2.3%, p < 0.001) 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Ravi et al [39] found that THA reduced health care costs about the index admission 1 year after surgery, relative to HA. Dangelmajer et al [9] found that patient's age and medical care payer status were all associated with odds of receiving THA, and patients with private insurance had higher odds of receiving THA. Reducing costs after hip fracture surgery should focus on improving the duration and efficiency of the rehabilitation phase.…”
Section: Costmentioning
confidence: 99%